STUDENTS’ EXPERIENCES AND OPINIONS ON USING TIKTOK FOR ENGLISH LEARNING - Intan Mulia; Zaiturrahmi Zaiturrahmi; Novita Diana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2026)
This study aimed to investigate students’ experiences and opinions on using TikTok for English learning. A qualitative case study design was employed involving 30 second-grade senior high school students at Sukma Bangsa Pidie. Data were collected through a Likert-scale questionnaire and semi-structured interviews. The questionnaire data were analyzed using descriptive statistical analysis, while the interview data were analyzed using thematic analysis. The findings showed that most students perceived TikTok as a useful and comfortable supplementary medium for learning English. TikTok supported vocabulary development, listening skills, and pronunciation through exposure to authentic English content and was considered enjoyable and engaging. However, challenges such as distractions from non-educational content and limited opportunities for active language production, particularly writing, were also identified. Overall, TikTok could serve as an effective supplementary medium for English learning when used appropriately, and both students and teachers were encouraged to use it selectively to maximize its educational benefits while minimizing potential distractions.